LEARNING PROCESSES IN THE ART OF MUSIC - Rasulova Saida Sabirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article contains information on all types of musical activity in the art of music, involuntary and involuntary attention, intense and effective mental activity in modern psychology on the content of attention on its qualitative characteristics.